PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI INFORMASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Nur Rohfitta; Ryan Radjendra; Sulastri; Idham Kholid; Bambang Sri Anggoro; Mujib; Mardiyah (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
This study aims to analyze the utilization of interactive learning media based on information technology in Islamic Religious Education learning. The development of digital technology has brought significant changes to the field of education, including the learning process in classrooms. Interactive learning media based on information technology provide opportunities for teachers to create more engaging, effective learning environments and to enhance student participation. This study employs a qualitative approach using a literature review method to examine various concepts, theories, and previous research related to the use of interactive learning media in Islamic Religious Education. The results indicate that the use of information technology-based interactive learning media can increase students' learning motivation, conceptual understanding, and active involvement in the learning process. In addition, technology-based media support the creation of more contextual and innovative learning environments that align with the characteristics of the digital generation. Therefore, the utilization of interactive learning media based on information technology becomes an important strategy in improving the quality of Islamic Religious Education learning in the digital era.